Elucidating the impact of biochar with different carbon/nitrogen ratios on soil biochemical properties and rhizosphere bacterial communities of flue-cured tobacco plants - Yang, Yingfen; Ye, Chenghu; Zhang, Wei; Zhu, Xiaohong; Li, Haohao; Yang, Dehai; Ahmed, Waqar; Zhao, Zhengxiong (Frontiers in Plant Science, 2023)
Background and aims In agriculture, biochar (BC) and nitrogen (N) fertilizers are commonly used for improving soil fertility and crop productivity. However, it remains unclear how different levels of BC and N fertilizer affect soil fertility and crop productivity. Methods This study elucidates the impact of different application rates of BC (0, 600, and 1200 kg/ha) and N fertilizer (105 and 126 kg/ha) on biomass accumulation, soil microbial biomass of carbon (SMC) and nitrogen (SMN), and soil biochemical properties, including soil organic carbon (SOC), total nitrogen (TN), soil nitrate nitrogen (NO3−−N), ammonium nitrogen (NH4+−N), urease (UE), acid phosphatase (ACP), catalase (CAT), and sucrase (SC) of tobacco plants. In addition, a high throughput amplicon sequencing technique was adopted to investigate the effect of different application rates of BC/N on rhizosphere bacterial communities of tobacco plants. Results The results confirm that high dosages of BC and N fertilizer (B1200N126) significantly enhance dry matter accumulation by 31.56% and 23.97% compared with control B0N105 and B0N126 under field conditions and 23.94% and 24.52% under pot experiment, respectively. The soil biochemical properties, SMC, and SMN significantly improved under the high application rate of BC and N fertilizer (B1200N126), while it negatively influenced the soil carbon/nitrogen ratio. Analysis of rhizosphere bacteriome through amplicon sequencing of 16S rRNA revealed that the structure, diversity, and composition of rhizosphere bacterial communities dramatically changed under different BC/N ratios. Proteobacteria, Bacteroidetes, Actinobacteria, Firmicutes, and Acidobacteria were highly abundant bacterial phyla in the rhizosphere of tobacco plants under different treatments. Co-occurrence network analysis displayed fewer negative correlations among rhizosphere bacterial communities under high dosages of biochar and nitrogen (B1200N126) than other treatments, which showed less competition for resources among microbes. In addition, a redundancy analysis further proved a significant positive correlation among SMC, SMN, soil biochemical properties, and high dosage of biochar and nitrogen (B1200N126). Conclusions Thus, we conclude that a high dosage of BC (1200 kg/ha) under a high application rate of N fertilizer (126 kg/ha) enhances the biomass accumulation of tobacco plants by improving the soil biochemical properties and activities of rhizosphere bacterial communities.